Effect Of Work Stress And Workload On Employee Performance Mediated By Job Satisfaction - Lena Mariska; Sulaiman Helmi (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
Employee performance will continue to increase if they are happy at work. Workload and work stress areindicators of job satisfaction. This study aims to analyze the Effect of Work Stress and Workload on PerformanceMediated by Job Satisfaction Employees of the Employment Social Security Administering Body. The researchmethod used in this research is explanatory. The simple random sampling technique was used to select 100 employeesof the Palembang Branch of Employment BPJS. The research instrument was a questionnaire that had beentested by CFA for both reliability and validity. In this study, the PLS-SEM technique was applied to test complexcausality models. The findings of this study resulted in a conceptual fit model which indicates that job satisfactiondoes not act as a mediator in the influence of work stress and workload. These results can help organizations,especially the Palembang Branch of Employment BPJS in increasing employee productivity.